Building skills in cognitive behavioral supervision - Prasko, Jan; Abeltina, Marija; Ociskova, Marie; Gecaite-Stonciene, Julija; Liska, Roman; Juskiene, Alicja; Slepecky, Milos; Bagdonaviciene, Lina (Neuro-endocrinology letters, 2024)
The purpose of supervision is to ensure that clients' needs are met and to monitor the effectiveness of therapeutic interventions and the therapeutic relationship. Cognitive behavioural therapy (CBT) supervision is the systematic cooperation of the supervisee with the supervisor, which aims at increasing the therapists' competencies when working with specific clients. The advantage of supervision is the possibility to shape and develop the therapist's practical skills through specific techniques. This paper aims to review currently available CBT supervision strategies that boost the development of therapists' skills and provide possible examples. Various techniques are discussed, including behavioural, cognitive, imagery and psychodrama methods that facilitate supervisors in enhancing therapists' skills. In addition, complementary approaches are discussed, such as role-playing, modelling, chaining, or imitation to present at a particular moment of the therapy, increase the insight into the client's perspective or the treatment itself, and search for an alternative approach to improve the therapeutic outcomes for the client. Overall, the article describes the supervisor's need to have a flexible variety of skills and know which learning methods might be most effective for boosting the supervisee's skill level and needs with a particular client.
Keywords: kognitivně behaviorální terapie; Behavior Therapy; lidé; klinické kompetence; Clinical Competence; behaviorální terapie; Cognitive Behavioral Therapy; Humans